Role of canonical and noncanonical autophagy pathways in shaping the life journey of B cells - Wang, Yiwen; Wu, Lan; Van Kaer, Luc (Frontiers in Immunology, 2024)
Autophagy is a regulated intracellular catabolic process by which invading pathogens, damaged organelles, aggregated proteins, and other macromolecules are degraded in lysosomes. It has been widely appreciated that autophagic activity plays an important role in regulating the development, fate determination, and function of cells in the immune system, including B lymphocytes. Autophagy encompasses several distinct pathways that have been linked to B cell homeostasis and function. While B cell presentation of major histocompatibility complex (MHC) class II-restricted cytosolic antigens to T cells involves both macroautophagy and chaperone-mediated autophagy (CMA), plasma cells and memory B cells mainly rely on macroautophagy for their survival. Emerging evidence indicates that core autophagy factors also participate in processes related to yet clearly distinct from classical autophagy. These autophagy-related pathways, referred to as noncanonical autophagy or conjugation of ATG8 to single membranes (CASM), contribute to B cell homeostasis and functions, including MHC class II-restricted antigen presentation to T cells, germinal center formation, plasma cell differentiation, and recall responses. Dysregulation of B cell autophagy has been identified in several autoimmune and autoinflammatory diseases such as systemic lupus erythematosus, rheumatoid arthritis, and inflammatory bowel disease. In this review, we discuss recent advances in understanding the role of canonical and noncanonical autophagy in B cells, including B cell development and maturation, antigen processing and presentation, pathogen-specific antibody responses, cytokine secretion, and autoimmunity. Unraveling the molecular mechanisms of canonical and noncanonical autophagy in B cells will improve our understanding of B cell biology, with implications for the development of autophagy-based immunotherapies.